Republika Federalna Niemiec wobec zachodniej granicy Polski w latach 1989-1991 = The Federal Republic of Germany's attitude towards Poland's western border in the years 1989-1991 - Hładkiewicz, Wiesław; Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As a result of the Round Table Agreement and the election of 1989 Poland appointed a noncommunist government led by Prime Minister Tadeusz Mazowiecki. The changes occurring in Poland were noted by the authorities of the Federal Republic of Germany. They were willing to make various reconciliation gestures, but were avoiding any binding declarations when it comes to recognizing Poland's western borders.
Keywords: Niemiecka Republika Federalna; Polska; polityka międzynarodowa; 1944-1989